T3 Cardiac arrhythmia resulting from an accumulation of branched chain amino acids in a mouse line with a mutation in bcat2. (21st March 2018) - Nicol, T; Podliesna, S; Portero, V; Falcone, S; Blease, A; Casini, S; Bezzina, CR; Remme, CA; Potter, P
Abstract : As part of a large-scale phenotype-driven screen we identified a line exhibiting sudden death. Mapping and whole genome sequencing identified a missense mutation in the Bcat2 gene, encoding mitochondrial branched chained aminotransferase, resulting in an early stop (Q300*) and a truncated protein. Homozygous mice exhibited increased plasma and urine levels of branched chain amino acids (BCAAs). Mutations in this pathway have previously been associated with Maple Syrup Urine Disease (MSUD) and can result in neurological symptoms. All homozygous mice died suddenly at 7 weeks of age, without any preceding symptoms. No cardiac abnormalities were observed on histological analysis, nor were there any other significant findings related to MSUD. An accumulation of branched chain amino acids was identified in urine and serum from homozygous mice, but unlike MSUD there was no accumulation of branched chain keto-acids. Homozygous mice showed QTc-prolongation in vivo on surface ECG analysis and prolonged action potential duration (APD) ex vivo (assessed by optical mapping in isolated hearts). Moreover, isolated hearts from mutant animals displayed increased inducibility of atrial and ventricular arrhythmias. In line with this, patch clamp measurements revealed significant APD90 prolongation and increased incidence of pro-arrhythmic events in isolated cardiomyocytes which was prevented by pharmacological inhibition of the late sodium current. Our current data suggests a direct effect of the mutation on cardiac function rather than the observed phenotypes resulting from an accumulation of BCAAs. Thus we have identified a novel model of sudden cardiac death resulting from abnormal BCAA metabolism.